Abrasive Materials (MATERIALS MINERALS YEARBOOK-1992) - Gordon T. Austin (The National Institute for Occupational Safety and Health (NIOSH), 1992)
The combined value of production of natural abrasives, which include tripoli, special silica stone, garnet, staurolite, and emery, decreased about 24% in 1992. The decrease in the value of tripoli production was the result of a decrease in total production. Emery decreased owing to a decrease in the volume of the material produced. Special silica stone experienced a significant increase in unit value and decrease in the quantity produced. Garnet showed a 6 % increase in quantity and a 36 % decrease in unit value. Staurolite decreased about 27 % in the quantity produced and value compared with those of 1991. The fused aluminum oxide industry showed a slight increase in the quantity produced and a 4 % increase in the value of production. The silicon carbide industry saw a 7 % increase in the quantity produced and a 10 % increase in the value of production. Combined, the industries increased 4 % in quantity and 6 % in value compared with those of 1991.